(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The formation of healthy lifestyle consciousness has become a strategic priority in New Uzbekistan, where socio-political reforms, educational modernization, and human-centered development converge to shape a new cultural paradigm of well-being. This article examines the philosophical and anthropological foundations of a healthy lifestyle as a key factor of sustainable social development. From a philosophical standpoint, the concept of health is viewed not merely as a biological state but as an integrated dimension of human existence, encompassing ethical self-care, rational behavior, value-based choice, and harmonious interaction with society and the environment. By integrating classical philosophical insights with contemporary approaches to human development, the research reveals how healthy lifestyle consciousness becomes an essential component of personal identity, collective wellbeing, and the long-term progress of New Uzbekistan.